Investigating the effect of stereospecific fluorination on the potency and selectivity of the tricyclic antidepressant, imipramine - Ishika Jaitly; Henry Parkins; Oscar Stokoe; Olivia A. Clink; Nicholas W. Barnes; Simona S. Capomolla; Mariah R. Stavrou; Celine Valant; Nicola J. Smith; Luke Hunter (Journal of Fluorine Chemistry, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Spatially explicit estimates of global population potential for leopard (Panthera pardus) - Sandy A. Slovikosky; Lisanne S. Petracca; Luke T. B. Hunter; Jacqueline L. Frair (Biodiversity and Conservation, 2025)
Many studies have assessed local densities of threatened carnivore species, but few have synthesized existing data into range-wide estimates based on habitat potential. Identifying where observed densities differ from expected values may help focus conservation attention. Herein, we related published leopard density estimates and a random selection of 0 values from across their extirpated range ( N = 209) to environmental and anthropogenic drivers. We then produced a spatially explicit estimate of expected density throughout the contemporary range of this species. We compared 16 candidate models that weighed density estimates by the inverse of their standard error, controlled for study design effects, and included spatial covariates at their optimal scale as determined by Akaike’s Information Criterion. Expected leopard density ranged from 0 to 8 individuals/100 km 2 and was positively and strongly related to the proportion of protected area at the 5-km scale, less so to the proportion of developed land cover (5-km), and negatively associated with human density (1-km), temperature (20-km), and longitude. Prediction error ranged from 0 to 12 leopards/100 km 2 , being greatest in India and its bordering countries. Overall, our model produced an expected value of 131,300 (42,692–428,498 95% CI) leopards globally. We predicted high expected densities in southern and eastern Africa where many published studies originate. Central and West Africa also hold high potential but lack estimates. Fine-scale variables and legacies of armed conflict that have depleted biodiversity should be considered when evaluating contemporary species status, and our predictions may highlight areas where conservation action could be most effective.

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Cheetah spatiotemporal overlap with other large carnivores and prey at camera-trap sites: do they fit the niche-complementarity hypothesis? - Kristina L. Cornhill; Guy A. Balme; Luke T. B. Hunter; Graham I. H. Kerley (Mammalian Biology, 2023)
In guilds, such as the large predators, species compete over multiple resources that are both consumable and non-consumable. The niche complementary hypothesis states that competitors can overlap in resource use if there is low overlap for at least one shared resource. In Africa, cheetah, Acinonyx jubatus , compete with other large carnivores across space, time and prey and are known to be subordinate; however, rarely has the entire guild been considered when assessing resource partitioning by cheetah. Using camera-trap data from four areas sampled over 4 years, we compared spatial and temporal overlap between cheetah and other large carnivores. Moreover, we estimated short-term avoidance of sites by cheetah after another large carnivore had visited. We show that cheetah align with the niche complementary hypothesis to avoid other large carnivores. Cheetah experienced high overlap with African wild dog, Lycaon pictus, activity patterns but avoided sites that were used frequently by them. The inverse was observed for lion, Panthera leo , and spotted hyena, Crocuta crocuta , with cheetah avoiding them across time but not space. Cheetah experienced moderate overlap with leopard, Panthera pardus, across both space and time, with only possible short-term avoidance occurring. Finally, cheetah exhibited high levels of spatial and temporal overlap with preferred prey species, suggesting a novel demonstration of the trade-off between resource acquisition and predator avoidance. Our results showcase the importance of taking multiple scales and resource axes into consideration when determining species abilities to co-exist and provides tools for managers working in highly managed systems.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Just a cat fight or something more sinister? Infanticide is rare among female leopards - Nikki le Roex; Andrew Bartlet; Luke T. B. Hunter; Guy A. Balme (Ecology, 2023)

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

The potential and shortcomings of mitochondrial DNA analysis for cheetah conservation management - René Meißner; Sven Winter; Uta Westerhüs; Alexander Sliwa; Carola Greve; Lena Godsall Bottriell; Paul Bottriell; Carlos Rodríguez Fernandes; Paul Vercammen; Luke T. B. Hunter; Alexei V. Abramov; Leili Khalatbari; et al. (Conservation Genetics, 2023)
There are only about 7,100 adolescent and adult cheetahs ( Acinonyx jubatus ) remaining in the wild. With the majority occurring outside protected areas, their numbers are rapidly declining. Evidence-based conservation measures are essential for the survival of this species. Genetic data is routinely used to inform conservation strategies, e.g., by establishing conservation units (CU). A commonly used marker in conservation genetics is mitochondrial DNA (mtDNA). Here, we investigated the cheetah’s phylogeography using a large-scale mtDNA data set to refine subspecies distributions and better assign individuals to CUs. Our dataset mostly consisted of historic samples to cover the cheetah’s whole range as the species has been extinct in most of its former distribution. While our genetic data largely agree with geography-based subspecies assignments, several geographic regions show conflicting mtDNA signals. Our analyses support previous findings that evolutionary forces such as incomplete lineage sorting or mitochondrial capture likely confound the mitochondrial phylogeography of this species, especially in East and, to some extent, in Northeast Africa. We caution that subspecies assignments solely based on mtDNA should be treated carefully and argue for an additional standardized nuclear single nucleotide polymorphism (SNP) marker set for subspecies identification and monitoring. However, the detection of the A. j. soemmeringii specific haplogroup by a newly designed Amplification-Refractory Mutation System (ARMS) can already provide support for conservation measures.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Genomic analyses show extremely perilous conservation status of African and Asiatic cheetahs ( Acinonyx jubatus ) - Stefan Prost; Ana Paula Machado; Julia Zumbroich; Lisa Preier; Sarita Mahtani‐Williams; Rene Meissner; Katerina Guschanski; Jaelle C. Brealey; Carlos Rodríguez Fernandes; Paul Vercammen; Luke T. B. Hunter; Alexei V. Abramov; et al. (Molecular Ecology, 2022)
We live in a world characterized by biodiversity loss and global environmental change. The extinction of large carnivores can have ramifying effects on ecosystems like an uncontrolled increase in wild herbivores, which in turn can have knock‐on impacts on vegetation regeneration and communities. Cheetahs ( Acinonyx jubatus ) serve important ecosystem functions as apex predators; yet, they are quickly heading towards an uncertain future. Threatened by habitat loss, human‐wildlife conflict and illegal trafficking, there are only approximately 7100 individuals remaining in nature. We present the most comprehensive genome‐wide analysis of cheetah phylogeography and conservation genomics to date, assembling samples from nearly the entire current and past species' range. We show that their phylogeography is more complex than previously thought, and that East African cheetahs ( A. j. raineyi ) are genetically distinct from Southern African individuals ( A. j. jubatus ), warranting their recognition as a distinct subspecies. We found strong genetic differentiation between all classically recognized subspecies, thus refuting earlier findings that cheetahs show only little differentiation. The strongest differentiation was observed between the Asiatic and all the African subspecies. We detected high inbreeding in the Critically Endangered Iranian ( A. j. venaticus ) and North‐western ( A. j. hecki ) subspecies, and show that overall cheetahs, along with snow leopards, have the lowest genome‐wide heterozygosity of all the big cats. This further emphasizes the cheetah's perilous conservation status. Our results provide novel and important information on cheetah phylogeography that can support evidence‐based conservation policy decisions to help protect this species. This is especially relevant in light of ongoing and proposed translocations across subspecies boundaries, and the increasing threats of illegal trafficking.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Contrasting climate velocity impacts in warm and cool locations show that effects of marine warming are worse in already warmer temperate waters - Philina A. English; Eric J. Ward; Christopher N. Rooper; Robyn E. Forrest; Luke A. Rogers; Karen L. Hunter; Andrew M. Edwards; Brendan M. Connors; Sean C. Anderson (Fish and Fisheries, 2022)
Species responses to climate change are often measured at broad spatiotemporal scales, which can miss the fine‐scale changes that are most relevant to conservation and fisheries management. We develop a scaleable geostatistical approach to assess how juvenile and adult fish distributions have been shaped by changes in bottom temperature and dissolved oxygen over a recent decade of warming in the northeast Pacific. Across 38 demersal fishes, biomass trends were associated negatively with warming and positively with dissolved oxygen, but when trends in both biomass and climate were converted to velocities—the speed and direction a population would have to move to maintain consistent conditions—the effect of temperature change differed depending on local conditions. In the warmest locations, warming velocities were associated with negative biotic velocities for 19 of 69 species‐maturity combinations, and yet were almost always associated with stable or positive biotic velocities in the coolest locations (64 of 69). These spatially consistent biomass declines (negative biotic velocities) in the warmest locations and increases in cooler locations suggest a redistribution of species with the potential for new ecological and fisheries interactions. After controlling for temperature, the more spatially consistent effects of dissolved oxygen were often negative, suggesting a mechanism other than hypoxia avoidance—potentially changes in primary production. Our approach identifies the species and locations that are most sensitive to observed changes in the environment at any scale, thus facilitating future vulnerability assessments.

Is there low maternal genetic variation in West Asian populations of leopard? - Mohammad S. Farhadinia; Mohammad Reza Ashrafzadeh; Helen Senn; Sohrab Ashrafi; Hamid Farahmand; Muhammad Ghazali; Luke T. B. Hunter; David W. Macdonald (Mammal Research, 2020)
Persian leopards Panthera pardus saxicolor have been extirpated from over 84% of their historic range and are now limited to rugged landscapes of West Asia and the Caucasus. Understanding and maintaining genetic diversity and population connectivity is important for preventing inbreeding and genetic drift, both of which can threaten population viability. All previous analyses of intraspecific genetic variation of West Asian leopards based on the NADH dehydrogenase subunit 5 gene have reported low mitogenomic diversity. In the current study, we sequenced 959 bp of the mtDNA cytochrome b gene to describe the spatial genetic structure of 22 wild Persian leopards across Iran, which hosts most of the subspecies extant range. The findings based on phylogenetic trees and median-joining network indicated that leopards from Iran formed a distinct subclade, i.e., P. p. saxicolor . The AMOVA analysis showed significant differentiation (88.55%) between the subclades of Persian leopards and other Asian leopards. The lowest levels of haplotype (0.247) and nucleotide (0.00078) diversity were estimated in Persian leopards from Iran. Mitochondrial genome sequencing revealed only two closely related haplotypes. There was no evidence for recent sudden demographic expansion scenario in Persian leopards. The low diversity in cytochrome b gene could potentially be brought about by selective pressure on mitochondria to adapt to oxidative stress and higher metabolic rates in cold environments.

Activity modification in heat: critical assessment of guidelines across athletic, occupational, and military settings in the USA - Yuri Hosokawa; Douglas J. Casa; Juli M. Trtanj; Luke N. Belval; Patricia A. Deuster; Sarah M. Giltz; Andrew J. Grundstein; Michelle D. Hawkins; Robert A. Huggins; Brenda Jacklitsch; John F. Jardine; Hunter Jones; et al. (International Journal of Biometeorology, 2019)

The critically endangered Asiatic cheetah Acinonyx jubatus venaticus in Iran: a review of recent distribution, and conservation status - Mohammad S. Farhadinia; Luke T. B. Hunter; Alireza Jourabchian; Fatemeh Hosseini-Zavarei; Hasan Akbari; Hooshang Ziaie; George B. Schaller; Houman Jowkar (Biodiversity and Conservation, 2017)

The importance of refugia, ecological traps and scale for large carnivore management - Ross T. Pitman; Lourens H. Swanepoel; Luke Hunter; Rob Slotow; Guy A. Balme (Biodiversity and Conservation, 2015)

To track or to call: comparing methods for estimating population abundance of African lions Panthera leo in Kafue National Park - Neil Midlane; M. Justin O’Riain; Guy A. Balme; Luke T. B. Hunter (Biodiversity and Conservation, 2015)

The Diasporin Pathway: a tumor progression-related transcriptional network that predicts breast cancer survival - Nigel P. S. Crawford; Renard C. Walker; Luanne Lukes; Jennifer S. Officewala; Robert W. Williams; Kent W. Hunter (Clinical & Experimental Metastasis, 2008)

Metastasis Predictive Signature Profiles Pre-exist in Normal Tissues - Haiyan Yang; Nigel Crawford; Luanne Lukes; Richard Finney; Mindy Lancaster; Kent W. Hunter (Clinical & Experimental Metastasis, 2005)

Caffeine suppresses metastasis in a transgenic mouse model: a prototype molecule for prophylaxis of metastasis - Haiyan Yang; Jessica Rouse; Luanne Lukes; Mindy Lancaster; Timothy Veenstra; Ming Zhou; Ying Shi; Yeong-Gwan Park; Kent Hunter (Clinical & Experimental Metastasis, 2005)

Comparative sequence analysis in eight inbred strains of the metastasis modifier QTL candidate gene Brms1 - Yeong-Gwan Park; Luanne Lukes; Howard Yang; Michael T. Debies; Rajeev S. Samant; Danny R. Welch; Maxwell Lee; Kent W. Hunter (Mammalian Genome, 2002)